The impact of magnetic play on early childhood social skills: one group pre-test-post-test experimental design - Mappapoleonro, Andi Musda; Malik, Hisham Abdul; Nadar, Wahyuni (Nashir Al-Kutub Indonesia, 2024)
This study aimed to determine the effect of using magnetic toys on children's social skills. Magnetic toys were chosen because they could stimulate interaction and cooperation among children while playing. The study used a quantitative approach with a One Group Pre-test-Post-test experimental design. The sample consisted of 20 early childhood children from a Kindergarten, who were given treatment to play with magnetic toys through several sessions. The Paired Sample t-Test was employed to compare the means of the same group before and after the intervention. The results of the study showed that the average score before the magnetic toy treatment was 70%, and the average after treatment was 83.70%. This demonstrated a significant increase in children's social skills after the intervention, such as the ability to share, cooperate, and communicate with peers. The reliability analysis obtained a Cronbach's Alpha value of 0.983, indicating high reliability. The normality test showed that the data distribution in the regression analysis followed a normal distribution. Levene's test, at a significance level of 5%, was conducted. From the Homogeneity Test, the data showed Fo = 1.835 and Sig. = 0.260. It is recommended that educators integrate magnetic games into early childhood education programs as an interactive tool to promote essential social skills.